The practice of professional consulting - Verlander, Edward George (San Francisco : Jossey-Bass/Pfeiffer, 2012)
'Despite the size of the consulting industry and its attractiveness to business school graduates, there is a dearth of agreement about what constitutes'professionalism' in consulting. The Practice of Professional Consulting provides the most comprehensive introduction to the field of consulting, including a complete system of guidelines, and all the tools, templates, techniques, case studies, competencies, and assessments to become a professional consultant. Broad enough to be useful to anyone starting any kind of consulting business, yet specific in explaining typical client situations, this guide offers new and aspiring consultants with a perspective of the rules, roles, values, methods, and techniques used across firms in the consulting industry'--
Includes bibliographical references (p. 274-279) and index.
Keywords: Business consultants; Consulting firms